Expressions of Hybridity as Strategy for Malayan Nationalism: Selected Artworks in Modern Malayan Art - Emelia Ong Ian Li; Izmer Ahmad (Wacana Seni Journal of Arts Discourse, 2015)
his paper examines selected artworks produced by Malayan artists of Chinese descent during the 1950s and 1960s within the contexts of Malayan nationalism and cultural identity. Local art historical writing frequently discusses their works as individualistic journeys in art, detached from nationalistic discourse and derivative of Western artistic movements. By employing the notions of hybridity to re-examine their works, this paper argues that this misleading view of their works is based on essentialist and static conceptions of Malayan culture. In contrast, this paper demonstrates how the artists employed non-essentialist concepts of identity based on otherness rather than similarity, to construct a criterion for authenticity and belonging. It emphasises the agency of the artists as active participants in the making of the new Malayan nation state within the field of art. It posits their works collectively as expressions of hybridity as strategy for Malayan nationalism. Subsequently, the notion of hybridity enables the viewing of cultural exchanges and borrowings in art within a horizontal model of cultural development rather than a concentric one which privileges Western culture or Chinese culture at the centre. This research employs a qualitative research methodology based on primary and secondary resources. This includes semi-structured interviews, first-hand viewing of artworks at art galleries, state-owned museums and private collections; archival research and secondary sources such as books, exhibition catalogues, newspapers, journal articles and unpublished dissertations. The theoretical framework is interdisciplinary in approach, supplementing art historical methods with those from cultural studies. This approach is in line with methods of "the new art history" which avoids purely formalistic analysis and emphasises the importance of contextual analysis. This paper contributes not only to the writing and analysis of Malaysian modern art but may be viewed comparatively to other Southeast Asian modern art histories who share similarities in their employment of Western modern art and their search for a legitimate national cultural identity.